2012
DOI: 10.5116/ijme.5096.5d66
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of success on the written anesthesiology board certification examination

Abstract: Objectives: To determine whether information available prior to and during anesthesia residency training can predict American Board of Anesthesiology (ABA) Part 1 (Written) performance and help identify anesthesia residents at risk for failure. Methods: Retrospective analysis of 97 anesthesiology residents' academic files at a single Midwestern residency program. ABA Part 1 score was used as the dependent variable. Categorical demographic predictor variables included gender, under-represented minority status, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 48 publications
2
9
0
Order By: Relevance
“…Another study of 194 internal medicine residents to develop a predictive tool found that ITE scores correlated in all PGYs with the best predictive value in PGY-3, 3 and a study of 97 anesthesiology residents found that the ITE was a strong predictor of passing the written board examination. 4 Both studies, and their findings, were similar to ours.…”
Section: Discussionsupporting
confidence: 79%
“…Another study of 194 internal medicine residents to develop a predictive tool found that ITE scores correlated in all PGYs with the best predictive value in PGY-3, 3 and a study of 97 anesthesiology residents found that the ITE was a strong predictor of passing the written board examination. 4 Both studies, and their findings, were similar to ours.…”
Section: Discussionsupporting
confidence: 79%
“…All first‐time test takers of the part 1 ABPMR‐CE during the 5‐year period from 2010 to 2014 who took at least 1 SAE‐R in the PGY3 or PGY4 (final) year of training were included in the sample. PGY 2 scores were not included because residents at that level of training would have had only 6 months of clinical training, because of wide variation in clinical experiences across residency programs in the first 6 months of training, and because previous publications have noted the strongest correlation for later years in training [1,6,7]. The ABPMR provided the AAPM&R with the names and residency programs of all first‐time test‐takers of the part 1 ABPMR‐CE in the years 2010 through 2014.…”
Section: Methodsmentioning
confidence: 99%
“…In the United States, many medical specialties offer residents the opportunity to take a national examination for self‐assessment purposes, and some have reported on the relationship between in‐training examinations and board certification [1‐10]. In some specialties, the examination is administered by the certifying board [1,3,7] and in others by a specialty society [2,4‐6,8‐10].…”
Section: Introductionmentioning
confidence: 99%
“…This was not entirely surprising, since 6 of 11 studies summarized in the literature review that included gender as a predictor variable did not find it to be statistically significant. 9,[19][20][21][22][23] The studies that did find statistically significant relationships observed that males performed better than females. 16,18,[24][25][26] However, further analysis revealed that the studies that reported statistical significance tended to have larger sample sizes, ranging from 273 to 5208.…”
Section: Discussionmentioning
confidence: 99%
“…16,18,[24][25][26] However, further analysis revealed that the studies that reported statistical significance tended to have larger sample sizes, ranging from 273 to 5208. 16,18,[24][25][26] The studies that did not report statistical significance by gender had sample sizes ranging from 77 to 175, 19,20,22,23 with the exception being one study with a sample size of 505. 9 It is unclear whether statistically significant relationship by gender might be observed on the prosthetics certification examination if a larger sample size was available to study.…”
Section: Discussionmentioning
confidence: 99%